Estudio del Perfil Fitoquímico y posibles aplicaciones de los extractos alcohólicos, etéreo y acuoso del Sunfo (clinopodium nubigenum (kunth) kuntze) - Illescas Bayas, Adriana Mishel (2020)
The research project aimed to carry out a study of the phytochemical profile of sunfo (Clinopodium nubigenum kunt kuntze) which is an endemic plant of the páramos of Ecuador, used ancestrally to heal digestive disorders and relieve pain, but unfortunately little research has been carried out. about it. Drying kinetics were carried out at 40 ° C for 48 hours, which allowed the plant to conserve its active compounds. Subsequently, in the laboratories of the CAREN faculty, the dry sample was ground in order to reduce the size of its particles and thus obtain the homogeneous crude drug powder, after which an extraction of active principles was carried out using 3 different types of solvents: ethyl ether 99%, ethanol ≥ 70% and distilled water. Certain characteristics of pH, total solids, odor, color and homogeneity could be evidenced in each of the extracts. Through a phytochemical screening carried out at the University of Havana (Cuba), the following active principles were found in the crude drug extract: fatty compounds, alkaloids, lactonic grouping, triterpenes / steroids, catechins, saponins, phenolic compounds, quinones / benzoquinones, flavonoids, mucilages, bitter principles, which are important compounds both for the pharmaceutical field and for the agro-industrial field.